Financial inclusion, competition and banking stability: Evidence from MENA countries - Alshihab, Salem (The Economics and Finance Letters, 2025)
Prior studies have shown in the finance industry that bank stability and financial inclusion are related, but the study on the role of the financial sector in influencing this relationship remains underexplored. This study aims to determine whether increased access to financial services leads to greater stability or introduces risks to the concentrated banking market. The research examines panel data from 96 banks across 13 Middle Eastern and North African (MENA) countries between 2010 and 2022. The empirical methods employed include the system Generalized Method of Moments (GMM) and fixed-effects panel regressions. Principal component analysis (PCA) is used to develop a composite financial inclusion index that considers access, consumption, and depth. The findings indicate that financial inclusion, particularly the access component, has the potential to enhance bank stability. However, this stabilizing effect is less pronounced and may even invert under conditions of high market power of banks. These negative impacts are most significant in countries within the lowest quartile of financial inclusion, suggesting that increasing access to monetary services could inadvertently lead to systemic risks in less competitive banking systems. These results highlight the importance of aligning financial inclusion policies with measures that promote competition. For policymakers in the MENA region, the optimal approach to improving access involves offering services through branches, ATMs, and digital channels, complemented by regulatory reforms aimed at ensuring stability without introducing additional risks.